1987
DOI: 10.1002/jat.2550070410
|View full text |Cite
|
Sign up to set email alerts
|

Maternal toxicity, embryolethality and abnormal fetal development in CD‐1 mice following one oral dose of T‐2 toxin

Abstract: An experiment was undertaken to determine the teratogenic effect of oral administration of T-2 toxin, a trichothecene mycotoxin. Firstly, a dose response study using 0, 0.5, 1.0, 2.0, 3.0, 3.5 and 4.0 mg/kg T-2 toxin in propylene glycol, on day 9 of pregnancy, was undertaken. Maternal deaths and toxicity was noted in the 4.0 and 3.5 mg/kg groups post-toxin administration. These groups gained less weight throughout gestation than the rest of the groups, because no fetuses were found in the 4.0 mg/kg group and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…From the present study, we could not prove to what extent the placental dysfunction affects the fetal abnormalities and fetal growth retardation. It is known that some toxicants such as ENU [17], Ara-C [27], busulfan [10], T-2 toxin [22], azacytidine [15], adrenomedullin antagonist [26] etc., induce small placenta and fetal growth restriction in rats or mice, although their induced fetal abnormalities are different from the ones in 6-MP. Therefore, 6-MP-induced fetal abnormalities seem to be caused by its specific direct anti-proliferative effects during organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…From the present study, we could not prove to what extent the placental dysfunction affects the fetal abnormalities and fetal growth retardation. It is known that some toxicants such as ENU [17], Ara-C [27], busulfan [10], T-2 toxin [22], azacytidine [15], adrenomedullin antagonist [26] etc., induce small placenta and fetal growth restriction in rats or mice, although their induced fetal abnormalities are different from the ones in 6-MP. Therefore, 6-MP-induced fetal abnormalities seem to be caused by its specific direct anti-proliferative effects during organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis in the central nervous system and cartilage primordium was observed in the fetuses from dams treated with T-2 toxin 11,12,25 . In the present study on rats, single cell necrosis was observed in the nervous system and liver of fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that T-2 toxin has cytotoxic effects due to its inhibitory effects on protein synthesis and DNA synthesis, and these effects may produce necrosis/ apoptosis 9,10 . It is said that pregnant mice treated with T-2 toxin exhibited fetal death and fetotoxicity mainly in the central nervous and skeletal systems in addition to maternal toxicity [11][12][13] . In rats, it is reported that T-2 toxin passes the placenta and distributes to fetal tissues, resulting in an impairment of the immune system 14 .…”
Section: Introductionmentioning
confidence: 99%
“…T-2 toxin readily crosses the placenta, is distributed to the fetal tissues 94 and induces fetal death, necrosis of the fetal brain and fetal bone malformations 95 . In addition, thymic atrophy and decreases in the viability of hematopoietic progenitor cells in the liver and in the number of B cells have also been reported in fetuses from dams exposed to T-2 toxin 41,43 .…”
Section: Fetal Tissuesmentioning
confidence: 99%
“…Moreover, changes attributable to T-2 toxin-treatment have been reported in the nervous system, liver, gastrointestinal tract and cartilage primordium in rat fetuses 96,97 . Bone malfomations such as incomplete ossification, absence of bones, wavy bones and fused bones 95,[98][99][100] may be related to the induction of apoptosis in the caudal half of the sclerotome around the notochord, and in the mesenchyme, chondroblasts and chondrocytes around the cartilage primordium detected in fetuses from dams treated with T-2 toxin 101 . Ishigami et al 102 first reported that T-2 toxin could induce apoptosis especially in the central nervous and skeletal systems after oral administration of T-2 toxin to pregnant mice (Fig.…”
Section: Fetal Tissuesmentioning
confidence: 99%